Inventory Control of Product Supply of Agricultural Product for Online Sales (Case Study in PT Insan Agritama Teknologi) - Meliyani, Evi Faridah Rostanti (Journal of Business on Hospitality and Tourism, 2019)
The industrial revolution 4.0 has encouraged a digital technology companies called startup. PT Insan Agritama Teknologi (Inagri) is one of startup in Bandung City that is engaged in agriculture as a supplier of food ingredients. Inventory of goods in Inagri is currently fulfilled from five partner farmers. At present, Inagri has collaborated with several Horeca (hotel, restaurant, café) and modern retailers to distribute agricultural products. However, for approximately 2.5 years, Inagri has not yet found a standard procedure for inventory control. Sometimes Inagri could not fulfill the demand because there was an out of stock of goods. Therefore required to control supplies. The purpose of this study was to identify the process of controlling inventory in Inagri and analyzed the classification of inventory in Inagri based on ABC analysis. This study used the ABC analysis method. The results showed that the classification of goods inventory in Inagri based on ABC analysis, group A amounted 16 commodities, this amount represented 21% of total items (76 commodities). Group B amounted 17 commodities or 22% of total commodity and group C had 43 items or 57% of total commodities sold by Inagri. ABC analysis is one of the solutions for making goods stock procurement decisions in future period.